PELAKSANAAN HANDOVER SHIFT PERAWAT MENGGUNAKAN KOMUNIKASI SBAR (SITUATION, BACKGROUND, ASSESSMENT, RECOMMENDATION) PADA PASIEN RISIKO JATUH DI RUMAH SAKIT SARI MULIA - M. Sobirin Mohtar; Yani Maulini; Sandi Suwardi (MNJ (Mahakam Nursing Journal), 2020)
Background: Patient safetyhas become a world issue that needs attention for health services. Patient safety is a basic principle of health services which views that safety is the right of every patient to receive service. Poor communication is the most common cause of side effects in all aspects of service. When communication in the consideration and acceptance is not done properly it can cause several problems such as the risk of falling and patient dissatisfaction. Objective: know the experience of nurses in making handovers through SBAR communication. Method: This study used a qualitative transcendent phenomenological approach to 10 participants in the inpatient room through a purposive sampling technique. Data were collected using in-dept interviews with a tape recorder and field notes. The analysis uses Colaizzi. Results: There were 7 themes found, namely (1) Nurses' understanding of the risk of falling. (2) Nurse's understanding of hand over. (3) Factors that influence the hand over. (4) Nurse's understanding of the SBAR communication method. (5) Benefits of nurses in using SBAR Communication. (6) Obstacles for nurses in doing hand over through SBAR (7) Meaning as a nurse for the success of their actions. Conclusion: There are various kinds of experiences of nurses in carrying out handovers on patients at risk of falling, starting from their understanding to the technique.